Challenges Facing The Gifted and Talented Learners With Hearing Imparment in Inclusive Education Programmes in Kenya - Okoth, Zedekia Onyango; Omoke, Charles Makori; Wachianga, Washington O. (Asian Journal of Science and Technology, 2019)
Inclusive education programmes for learners with special needs and disabilities are advocated for by international and national policy documents. However the existence of the gifted and talented learners who are hearing impaired in inclusive education programmes has had minimal attention. It was against that background that this paper was drawn to establish challenges facing inclusive education programmes for gifted and talented learners who are hearing impaired in Kenya. The study was guided by Critical Theory and it employed mixed methods approach. The research design was Concurrent Triangulation. The target population was 1 Principal, 28 teachers and 208 learners in a technical institution, 1 National Council for Persons with Disabilities officer, 2 Quality Assurance and Standards officers and 3 Educational Assessment and Research Center officers purposively sampled in Siaya County, Kenya. The research instruments were; interview schedule, questionnaire, focus group discussion, and observation checklist. The reliability of the research tools was ascertained through testretest and was calculated using Pearson’s correlation coefficient (r) to establish the extent to which the content of the instruments was consistent in eliciting the same responses to determine reliability of the research instruments. Content validity of the instruments was checked by experts who were my supervisors at Jaramogi Oginga Odinga University of Science and Technology. Qualitative data were analyzed by the use of content narrative and thematic analysis techniques and presented in direct quotes and narrative in line with the study objectives. Quantitative data were analyzed with the help of Statistical Package for Social Sciences (SPSS) computer programme version 22. It was significant to carry out the study because it could become a major source of reference to stakeholders. The major issue facing inclusive education for gifted and talented learners with hearing impairment in inclusive education programme revolved around insufficient resources. It was concluded that there was need to persuade all stakeholders to realize that gifted and talented learners with hearing impairment are worthy of an equal access to opportunities in inclusive education programmes.
Keywords: Gifted and Talented; Hearing impairment; Inclusive Education.